2010
DOI: 10.1142/s179352531000029x
|View full text |Cite
|
Sign up to set email alerts
|

Obstructions to the Existence and Squeezing of Lagrangian Cobordisms

Abstract: Abstract. Capacities that provide both qualitative and quantitative obstructions to the existence of a Lagrangian cobordism between two (n − 1)-dimensional submanifolds in parallel hyperplanes of R 2n are defined using the theory of generating families. Qualitatively, these capacities show that, for example, in R 4 there is no Lagrangian cobordism between two ∞-shaped curves with a negative crossing when the lower end is "smaller". Quantitatively, when the boundary of a Lagrangian ball lies in a hyperplane of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…) for L, where f − Λ − and f Λ − are in the same equivalence class (classes are defined up to stabilizations and fiber-preserving diffeomorphisms; for more details we refer to [19]). …”
Section: Proof Of Theorem 15mentioning
confidence: 99%
See 2 more Smart Citations
“…) for L, where f − Λ − and f Λ − are in the same equivalence class (classes are defined up to stabilizations and fiber-preserving diffeomorphisms; for more details we refer to [19]). …”
Section: Proof Of Theorem 15mentioning
confidence: 99%
“…The way to glue two cobordisms which admit tame, compactible triples of generating families is written in [19].…”
Section: Proof Of Theorem 15mentioning
confidence: 99%
See 1 more Smart Citation
“…The notion of length, however, does not seem to have an analogue in the non-relative case. In fact, an interesting feature of the length is that it arises from a 1-dimensional measurement rather than the usual 2-dimensional measurements that appear in non-squeezing theorems, even in the case of Lagrangian cobordisms [39].…”
mentioning
confidence: 99%
“…Our capacities are derived from a filtered version of Legendrian Contact Cohomology, linearized by an augmentation ε; these capacities are, in a sense, monotonic under Lagrangian cobordism. Note that this framework -though not the actual construction -is similar to that used in for slices of "flat-at-infinity" Lagrangians [39] and to Hutchings ECH capacities [30]. More specifically, for each linearized Legendrian Contact Cohomology class θ ∈ LCH * (Λ, ε), we define a quantity c(Λ, ε, θ) ∈ (0, +∞] that, essentially, measures the Reeb height of the class θ. Ekholm showed that a Lagrangian cobordism L from Λ − to Λ + with an augmentation ε − for Λ − induces an augmentation ε + of Λ + and a map…”
mentioning
confidence: 99%